Anthelmintic and relaxant activities of Verbascum Thapsus Mullein - Ali Niaz; Ali Shah Syed; Shah Ismail; Ahmed Ghayour; Ghias Mehreen; Khan Imran; Ali Waqar (BMC, 2012)
Abstract Background Verbascum thapsus is used in tribal medicine as an antispasmodic, anti-tubercular agent and wormicide. In this study, we investigated the antispasmodic and anthelmintic activities of crude aqueous methanolic extract of the plant. Methods V. thapsus extracts were tested against roundworms (Ascaridia galli) and tapeworms (Raillietina spiralis). Each species of worm was placed into a negative control group, an albendazole treatment group, or a V. thapsus treatment group, and the time taken for paralysis and death was determined. In addition, relaxation activity tests were performed on sections of rabbit's jejunum. Plant extracts were tested on KCl-induced contractions and the relaxation activities were quantified against atropine. V. thapsus calcium chloride curves were constructed to investigate the mode of action of the plant extracts. Results We detected flavonoids, saponins, tannins, terpenoids, glycosides, carbohydrates, proteins, fats and fixed oils in V. thapsus. For both species of worm, paralysis occurred fastest at the highest concentration of extract. The relative index values for paralysis in A. galli were 4.58, 3.41 and 2.08, at concentrations of 10, 20 and 40 mg/ml of plant extract, respectively. The relative index for death in A. galli suggested that V. thapsus extract is wormicidal at high concentration. Similarly, the relative indexes for paralysis and death in R. spiralis suggested that the extract is a more potent wormicidal agent than albendazole. The mean EC50 relaxation activity values for spontaneous and KCl induced contractions were 7.5 ± 1.4 mg/ml (6.57-8.01, n = 6) and 7.9 ± 0.41 mg/ml (7.44-8.46, n = 6), respectively. The relaxation activity of the extract was 11.42 ± 2, 17.0 ± 3, 28.5 ± 4, and 128.0 ± 7% of the maximum observed for atropine at corresponding concentrations. The calcium chloride curves showed that V. thapsus extracts (3 mg/ml), had a mean EC50 (log molar [calcium]) value of -1.9 ± 0.06 (-1.87 - -1.98, n = 6) vs. control EC50 = -2.5 ± 0.12 (-2.37 - -2.56, n = 6), whereas the verapamil (0.1 μM) EC50 was -1.7 ± 0.1 (-1.6 - -1.8, n = 6) vs. control EC50 = -2.4 ± 0.09 (-2.3 - -2.47, n = 5). Conclusions Our results suggest that V. thapsus, which is currently used by some tribes in the Malakand region of Pakistan, has anthelmintic and antispasmodic value.